Plan logístico de exportación de pulpa de maracuyá a través de cobranza bancaria documentaria hacia el mercado de Estados Unidos. - Tocto Sanchez, Kerly Valeria (My University, 2021)
Throughout its history, Ecuador has been recognized worldwide as one of the agro-exporting countries in Latin America and every day it has managed to expand to new markets in order to establish international negotiations, this directly benefits the country by improving economic development and in the social sphere, these actions contribute to the creation of new jobs, partially decreasing the unemployment rate. Therefore, the objective of this document is to develop a logistics plan for the export of passion fruit pulp from Ecuador to the United States. For this purpose, a search for information was conducted in primary sources of scientific articles and official regulations, which facilitated the theoretical foundation of the subject and, consequently, the development of the logistics plan, with truthful information and real data obtained from the different search sources. Finally, the logistic export plan made it possible to discover a high demand for the product to be exported in the United States and demonstrated how important it is to choose the correct form of payment. In addition, this plan serves as a guide for Ecuadorian exporters of passion fruit pulp, since they can implement it within their companies, accelerating each of their processes and reducing possible costs and expenses.
Ecuador a lo largo de su historia ha sido reconocido a nivel mundial como uno de los países agroexportadores de Latinoamérica y cada día a logrado expandirse a nuevos mercados con la finalidad de establecer negociaciones internacionales, esto beneficia directamente al país, ya que mejora el desarrollo económico y en el ámbito social, estas acciones contribuyen a la creación de nuevas plazas de trabajo disminuyendo parcialmente el índice de desempleo. Por lo tanto, este documento tiene como objetivo desarrollar un plan logístico para la exportación de pulpa de maracuyá desde Ecuador hacia los Estados Unidos, para ello, se realizó la búsqueda de información en fuentes primarias de artículos científicos y reglamentos oficiales, que facilitó la fundamentación teórica del tema y consiguiente a esto poder elaborar el plan logístico, con información veraz y datos reales obtenidos de las distintas fuentes de búsqueda. Finalmente, el plan logístico de exportación permitió descubrir una alta demanda del producto a exportar en los Estados Unidos y demostró lo importante que es elegir una correcta forma de pago, adicional a esto, este plan sirve como guía a los exportadores ecuatorianos de pulpa de maracuyá, ya que pueden implementarlo al interior de sus empresas, acelerando cada uno de sus procesos y reduciendo posibles costos y gastos.
Keywords: EXPORTACIÓN; LOGÍSTICA; ESTRATEGIAS; FORMA DE PAGO